EXPERIENTIAL MARKETING DAN SWITCHING BARRIERS TERHADAP CUSTOMER RETENTION DAN LOYALITAS PELANGGAN - Putri Nurjanah; Juanim Juanim (Faculty of Economic and Business, University of Pasundan, 2020)
Customer loyalty is the main aspect of the company that needs to be maintained through a good, consistent, and long-lasting strategy. This study aims to determine the influence of experiential marketing and switching barriers on customer retention and their impact on customer loyalty at the Supratman branch of Togamas bookstore, Bandung. The method used is descriptive and verification methods. Nonprobability sampling with incidental method was used with a sample size of 100 respondents. The data analysis method used is path analysis, multiple correlation, and the coefficient of determination. The results showed that experiential marketing, switching barriers, and customer retention at the Togamas bookstore were good, while customer loyalty was good enough. The direct effect of experiential marketing on customer loyalty is greater than the indirect effect through customer retention. The indirect effect of switching barriers on loyalty is greater than the direct effect.